Estimation of Some Breast Cancer Tumor Markers Using Flow cytometry - Khalid, Bossina Ahmed Ibrahim; Gouida, Mona Samy Othman; Youssef, Magdy Mahfouz; Youssef, Magdy Mahfouz; Al Kamel, Sameh Roshdy Abdel Aziz (Journal of medical and pharmaceutical sciences, 2017)
Objective: The aim of this study was to estimate some tumor markers such as caspase-3, caspase-8 and annexin-v levels in blood and tissue of patients with breast cancer and establishing the relation between these apoptotic markers level and response to chemotherapy. Materials and Methods: A number of 150 females were divided into four groups, malignant neoplasm of breast cancer included 50 females, that were diagnosed into stage I, II, III, and IV and included inflammatory breast carcinoma, infiltrating ductal carcinoma, infiltrating lobular carcinoma, ductal carcinoma in situ and lobular carcinoma in situ, control group included 50 females with normal breast, benign neoplasm of breast cancer included 25 cases that contained a heterogeneous group of lesions including developmental abnormalities, epithelial and stromal proliferations and neoplasms and follow up group (after chemotherapy) include 25 cases that her surgery was done and taken chemotherapy. Flow cytometry was used to analyze cell cycle, caspase-3, caspase-8 and annexin-v among the study groups. Results: The results showed that caspase 3 and caspases-8 expressions were significantly decreased in malignant group compared with the control group (P = 0.0028 and P =0.008), respectively; caspase 3 and caspase-8 levels decreased significantly in malignant group compared with the follow up group (P =0.001and P =0.0105), respectively; caspase 3 and caspases-8 levels were decreased in benign group compared with the control group (P = 0.041and P =0.512). Annexin-v was highly expressed in both tissues and blood of malignant groups in viable stage than benign compared with the normal groups (P = 0.01 and P = 0.006) respectively. Annexin-v level was highly expressed in both tissues and blood of malignant groups in necrotic stage compared with the control and follow up groups (P = 0.0001 and P = 0.01). But in early and late apoptotic phase follow up group annexin-v level was significantly increased more than the malignant group with (P=0.0001 and P=0.0026) respectively. Sub G1 apoptosis level in malignant and benign group significantly decreased compared with the follow up group (P = 0.0001 and P = 0.003) respectively. Our data showed that S phase level was significantly increased among malignant group compared with the control and follow up groups (P = 0.0001), also S phase level was increased significantly among benign group more than the control and follow up groups (P= 0.9 and P=0.003) respectively; and S phase was significantly decreased in benign group compared with the malignant blood and tissue groups (P = 0.03 and P=0.05) respectively. Conclusion: Annexin-v, caspase-3 and caspase-8 level in blood and tissue may serve as markers for the diagnosis of breast cancer and the response to chemotherapy. Also, S phase of cell cycle is one of the significant factors in the development of breast cancer.